Mean flow, eddy variability and energetics of the Subantarctic Front south of Australia - Phillips, HE (2000)
This thesis describes the variability and mean flow of the Subantarctic Front (SAF) south of Australia using time series measurements of velocity and temperature from 1993 to 1995, and six hydrographic transects along WOCE line SR3 from Tasmania to Antarctica over the period 1991 to 1996. The SAF is the strongest jet of the Antarctic Circumpolar Current (ACC) south of Australia. The time series of velocity and temperature are only the third such dataset collected in the ACC and provide insight into the dynamics of this massive current and into the heat and momentum balances of the Southern Ocean. The SAF was found to be an energetic, meandering jet with vertically coherent fluctuations. These fluctuations varied on a timescale of 20 days, and had a typical amplitude of 30 cm/s at 1150 dbar. The analysis used a coordinate frame that rotated daily to be in alignment with the direction of flow. This allowed the mesoscale variability of the SAF to be isolated from variability due to meandering of the front and proved very successful for examining eddy fluxes. Vertically averaged cross-stream eddy heat flux was 11.3 kW/m^2 poleward and was significantly different from zero at the 95% confidence level for fluctuations with periods between 2 and 90 days. Zonally integrated, this eddy heat flux (=0.9x10^15 W) is more than large enough to balance the heat lost south of the Polar Front and is as large as cross-SAF fluxes found in Drake Passage. Cross-stream eddy momentum fluxes were small and not significantly different from zero but were tending to decelerate the mean flow. A relationship between vertical motion and meander phase identified in the Gulf Stream was found to hold for the SAF. Eddy kinetic energy levels were similar to those in Drake Passage and southeast of New Zealand. Eddy potential energy was up to an order of magnitude larger than at the other ACC sites, most likely because meandering of the front is more common south of Australia. Baroclinic conversion was found to be the dominant mechanism by which ...